Closed-Loop Acoustic Stimulation During Sedation with Dexmedetomidine (CLASS-D): Protocol for a Within-Subject, Crossover, Controlled, Interventional Trial with Healthy Volunteers - Guay CS (Dove Medical Press, 2021)
Christian S Guay,1 Alyssa K Labonte,1 Michael C Montana,1 Eric C Landsness,2 Brendan P Lucey,2 MohammadMehdi Kafashan,1 Simon Haroutounian,1 Michael S Avidan,1,3 Emery N Brown,4,5 Ben Julian A Palanca1,3,6,7 1Department of Anesthesiology, Washington University School of Medicine in St. Louis, St. Louis, MO, USA; 2Department of Neurology, Division of Sleep Medicine, Washington University School of Medicine in St. Louis, St. Louis, MO, USA; 3Department of Psychiatry, Washington University School of Medicine in St. Louis, St. Louis, MO, USA; 4Department of Brain and Cognitive Sciences, Massachusetts Institute of Technology, Cambridge, MA, USA; 5Department of Anesthesia, Critical Care and Pain Medicine, Massachusetts General Hospital, Harvard Medical School, Boston, MA, USA; 6Division of Biology and Biomedical Sciences, Washington University School of Medicine in St. Louis, St. Louis, MO, USA; 7Department of Biomedical Engineering, Washington University in St. Louis, St. Louis, MO, USACorrespondence: Ben Julian A PalancaWashington University School of Medicine in St. Louis, Department of Anesthesiology, 660 S. Euclid Avenue, Box 8054, St. Louis, MO, 63110, USATel +1 314-273-9076Fax +1 314-747-3977Email palancab@wustl.eduIntroduction: The relative power of slow-delta oscillations in the electroencephalogram (EEG), termed slow-wave activity (SWA), correlates with level of unconsciousness. Acoustic enhancement of SWA has been reported for sleep states, but it remains unknown if pharmacologically induced SWA can be enhanced using sound. Dexmedetomidine is a sedative whose EEG oscillations resemble those of natural sleep. This pilot study was designed to investigate whether SWA can be enhanced using closed-loop acoustic stimulation during sedation (CLASS) with dexmedetomidine.Methods: Closed-Loop Acoustic Stimulation during Sedation with Dexmedetomidine (CLASS-D) is a within-subject, crossover, controlled, interventional trial with healthy volunteers. Each participant will be sedated with a dexmedetomidine target-controlled infusion (TCI). Participants will undergo three CLASS conditions in a multiple crossover design: in-phase (phase-locked to slow-wave upslopes), anti-phase (phase-locked to slow-wave downslopes) and sham (silence). High-density EEG recordings will assess the effects of CLASS across the scalp. A volitional behavioral task and sequential thermal arousals will assess the anesthetic effects of CLASS. Ambulatory sleep studies will be performed on nights immediately preceding and following the sedation session. EEG effects of CLASS will be assessed using linear mixed-effects models. The impacts of CLASS on behavior and arousal thresholds will be assessed using logistic regression modeling. Parametric modeling will determine differences in sleepiness and measures of sleep homeostasis before and after sedation.Results: The primary outcome of this pilot study is the effect of CLASS on EEG slow waves. Secondary outcomes include the effects of CLASS on the following: performance of a volitional task, arousal thresholds, and subsequent sleep.Discussion: This investigation will elucidate 1) the potential of exogenous sensory stimulation to potentiate SWA during sedation; 2) the physiologic significance of this intervention; and 3) the connection between EEG slow-waves observed during sleep and sedation.Keywords: sleep, anesthesia, consciousness, dexmedetomidine, electroencephalography, acoustic stimulation